TWO RARE TRAVELOGUES OF 18TH CENTURY - Dr. Rafaqat Ali Shahid; Dr. Muhammad Saeed; Bazghah Qandeel (Zaban-o-Adab, 2022)
This article is an analytic study of Dr Najeeb Arif’s book, entitled "janobi Aishyai Musalmanon Ka Tasawwur e Maghrib — 19win Sadi Ke 2 Nadir Safarnamy." (concept of the west in the Muslims of South Asia — two rare travelogues of 18th century). In this book editor Dr Najeeba Arif reproduced two rarest and unpublished Persian accounts of journey of 18th century about the travel experiences in South Asia and Europe. These two are as follows: Travel in Russia and China, by Muhammad Abdullah, written in approximately 1771. 2- Modern history (travels in Europe), by Munshi Ismail of Bengal, written in 1773. Editor of this book Dr Najeeba Arif searched in British libraries for her post-doctoral research project and discovered these two rarest Persian travelogues from Cambridge University library and McGill University library. She reproduced original manuscripts of these travelogues in this book along with Urdu translation of both. In addition the editor wrote a comprehensive preamble about and annotated notes on these travelogues. The Urdu translation of these Persian texts are made continuously by Dr Jawad Hamadani and Professor Sarfaraz Zafar. This book is a part of Dr. Najiba Arif’s research project. At the end of book, it comprises a useful index.